Developing of Singular and Plural Noun (SIPU) English Learning Media with Android-Based Applications at the Senior High School level - Rizky Amalia, Amanda; Mulyadi, Dodi; Ifadah, Muhimatul (English Language and Literature International Conference (ELLiC) Proceedings, 2024)
In this digital era, learning English has become easier because of the media that can be used such as learning applications, websites, content that contains English learning and one that is still often used is interactive learning media. Therefore, the innovation of the Singular and Plural Noun application where this application is a learning media that aims to facilitate student understanding in grammar material and increase student interest and creativity to measure their abilities. The method used in this research is research and development using ADDIE (Analyzing, Design, Development, Implementation, Evaluation). The subject of this current study was class XI superior to as many as 35 students at Senior High School 15 Semarang. The results showed that the media is valid and eligible to be implemented in teaching grammar, especially singular and plural nouns to eleventh grade students. The impact of this implementation is to increase students' interest in learning and make it easier for students to absorb material about singular and plural nouns. Based on the results of the implementation of learning media, this SIPU application is highly recommended for English learning media to provide an overview of digital media and make it easier for teachers in interactive learning.